Concurrent daily cisplatin and extended-field radiation therapy for carcinoma of the cervix. Issue 1 (1st January 2008) - Uno, T.; Mitsuhashi, A.; Isobe, K.; Yamamoto, S.; Kawakami, H.; Ueno, N.; Usui, H.; Tate, S.; Kawata, T.; Ito, H.
Abstract : The aim of this study was to assess acute toxicities of concurrent low-dose daily cisplatin and extended-field radiation therapy (EFRT) for carcinoma of the uterine cervix. Fifteen women with cervical cancer who were treated with concurrent daily low-dose cisplatin and EFRT were analyzed. Daily cisplatin dose was fixed to 8 mg/m 2, which was determined in the preceding phase I study using pelvic radiotherapy. Twelve patients underwent either combined external beam radiation therapy and intracavitary brachytherapy or external beam radiation therapy alone. Three other patients were treated with adjuvant chemoradiotherapy after surgery. A total dose of EFRT ranged from 40 to 45 Gy, with an additional boost to the gross tumor volume up to 50.4–55 Gy. A median total dose of cisplatin during entire radiation therapy course was 224 mg/m 2 (range, 200–240 mg/m 2 ). In 14 of 15 patients (93%), daily cisplatin could be delivered continuously as planned without any modification. Administration of cisplatin had to be interrupted in only one patient for only 3 days. Fourteen patients developed grade 2 or worse leukopenia including five after treatment, grade 2 in four, grade 3 in eight, and grade 4 in two. Grade 3 thrombocytopenia was observed in three patients. Grade 2 or worse anemia was observed in 12. Three patients had grade 3 nonhematologic toxicities, diarrhea in two, and nausea/vomiting in one. Although moderate to severe hematologic toxicities are common, this study suggests that concurrent low-dose daily cisplatin and EFRT are feasible. A cumulative cisplatin dose of greater than 200 mg/m 2 during radiation therapy could be achieved by using daily cisplatin dose of 8 mg/m 2 .